Penguatan Halal Value Chain dalam Pemasaran Abon Lele melalui Adaptasi Digital - Uliyatul Mu’awwanah; Atik Mardiyah; Aprilia Sri Utami (Mujtama': Jurnal Pengabdian Masyarakat, 2021)
Food and Beverage is included in the processing industry, nowadays its contribution has a positive effect on GDP. Halal food and drink has become a lifestyle trend for Muslims and even non-Muslims because the word halal also defines hygienic or clean. In Indonesia, with the majority of Muslims proclaiming themselves to be the center of sharia economic development in the eyes of the world, one of them is through the Halal Value Chain strategy. Meanwhile, the Pandemic disaster that was also experienced by Indonesia caused the entire economy to decline. The affected small residents are increasingly experiencing difficulties. This paper describes the mentoring program that has been carried out by the service provider in its function to push forward the pace of the economy through the creative idea of making Shredded Catfish, marketing it through social networks as well as educating the halal ecosystem.